2004
DOI: 10.1007/s10800-004-2728-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a magnesium?lithium alloy as an anode for magnesium batteries

Abstract: In this work, we describe an evaluation of an Mg-Li alloy (Li: 13 wt %) for possible use in magnesium primary reserve batteries. Higher OCP for the Mg-Li alloy have been observed in 2 M MgCl 2 and MgBr 2 electrolyte. The corrosion rate of the Mg-Li alloy is found to be in the order: MgCl 2 < Mg(COOCH 3 ) 2 < MgSO 4 < MgBr 2 < Mg(ClO 4 ) 2 . Mg-Li alloys exhibit higher (81%) anodic efficiencies even when the current density is increased to 8.6 mA cm )2 . It has been observed that Mg-Li/MgCl 2 /CuO cells offer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…In addition to the concerted efforts focused on the particles, morphologies, and surface film of Mg, alloying Mg with elements with a high hydrogen evolution overpotential is attracting growing attention. The Mgalloy prepared by doping pure magnesium with metals or elements (i.e., Al, Zn, Ga, Ca, Pb, Li, Mn, and rare earth elements) can effectively inhibit the HER and self-corrosion reactions of the anode, thereby facilitating the self-peeling of the discharge products and thus reducing the polarization of Mg anodes in aqueous electrolytes [22][23][24][25][26][27][28][29][30][31] . There have been many studies on Mg-Zn [22] , Mg-Ca [23] , commercial AZ31 (Mg-3%Al-1%Zn), AZ61 (Mg-6%Al-1%Zn) [24,25] , and AP65 (Mg-6%Al-5%Pb) [26] alloys serving as anodes for Mg-air batteries and significant effort has also been devoted to some other elements with high corrosion resistance [27][28][29][30][31][32][33][34] .…”
Section: Mg Alloysmentioning
confidence: 99%
“…In addition to the concerted efforts focused on the particles, morphologies, and surface film of Mg, alloying Mg with elements with a high hydrogen evolution overpotential is attracting growing attention. The Mgalloy prepared by doping pure magnesium with metals or elements (i.e., Al, Zn, Ga, Ca, Pb, Li, Mn, and rare earth elements) can effectively inhibit the HER and self-corrosion reactions of the anode, thereby facilitating the self-peeling of the discharge products and thus reducing the polarization of Mg anodes in aqueous electrolytes [22][23][24][25][26][27][28][29][30][31] . There have been many studies on Mg-Zn [22] , Mg-Ca [23] , commercial AZ31 (Mg-3%Al-1%Zn), AZ61 (Mg-6%Al-1%Zn) [24,25] , and AP65 (Mg-6%Al-5%Pb) [26] alloys serving as anodes for Mg-air batteries and significant effort has also been devoted to some other elements with high corrosion resistance [27][28][29][30][31][32][33][34] .…”
Section: Mg Alloysmentioning
confidence: 99%
“…14, 15 Udhayan et al reported that magnesium alloy AP65 (Al: 6-7%, Zn: 0.14-1.5%, Mn: 0.15-1.3% and Pb: 4.5-5%) has a hydrogen evolution rate of 0.15 mL min À1 cm À2 and a utilization efficiency of 84.6%. 17 They found that this Mg-Li alloy exhibited higher anodic efficiencies (81%) corresponding to the high current density (8.6 mA cm À2 ). 16 Sivashanmugam et al investigated Mg-Li alloy with 13 wt% Li for their possible use in magnesium primary reserve batteries.…”
Section: Introductionmentioning
confidence: 96%
“…16 Sivashanmugam et al investigated Mg-Li alloy with 13 wt% Li for their possible use in magnesium primary reserve batteries. 17 They found that this Mg-Li alloy exhibited higher anodic efficiencies (81%) corresponding to the high current density (8.6 mA cm À2 ). The other method of increasing the electrochemical properties of Mg-Li based alloys is the addition of additives to electrolytes.…”
Section: Introductionmentioning
confidence: 96%
“…In general, among various Mg alloy materials, the AZ31 alloy exhibits an excellent overall electrochemical performance, so it is often used as anode material for Mg‐air batteries in commercial products 4 . In addition, studies on various alloying elements (Mg, 5 Li, 6 Ga, 7 Ca, 8 and rare‐earth elements 2 ) are being actively conducted to improve the performance of the Mg alloy.…”
Section: Introductionmentioning
confidence: 99%